Ultraviolet absorption cross-section measurements of shock-heated O2 from 2, 000–8, 400 K using a tunable laser. (May 2020) - Krish, Ajay; Streicher, Jesse W.; Hanson, Ronald K.
Highlights: Spectroscopic model developed for the Schumann-Runge system. Spectroscopic model extends to high temperatures and non-equilibrium conditions. UV pulsed laser absorption spectroscopy acquired O2 absorption cross-sections. Developed steady-state model for vibrational temperature determination above 6000 K. Developed spectroscopic models agree with cross-section data up to 8400 K. Abstract: Accurate spectroscopic modeling is critical when measuring time-resolved, state-specific chemical kinetics of diatomic molecules. Here, a spectroscopic model (Stanford model) was developed to accurately simulate oxygen absorption cross-sections in the Schumann-Runge system for non-equilibrium conditions. Cross-sections of shock-heated oxygen (O2 ) have been measured using a picosecond pulsed ultraviolet (UV) laser, and the viability of two spectroscopic models has been demonstrated. Measurements were taken behind reflected shocks in 2% and 5% O2 in argon (Ar) mixtures around 211.2 nm and 236.9 nm up to initial post-reflected shock temperatures of 10, 700 K. Cross-sections were plotted against vibrational temperature and compared to calculated cross-sections from the Stanford model and the Adjusted Spectrum model. Vibrational temperatures for cross-section measurements were calculated for plateaus and peaks in experimental absorbances using a Bethe-Teller relaxation model up to 6, 000 K and a steady-state approach above 6, 000 K. Vibrational temperatures calculated using the steady-state approach were 3–5% higher than coupled vibration-dissociation (CVD) calculations. The experimental cross-sections agree to within 15% of the Stanford model for both wavelength regimes.